The Frequency of micronuclei in oral mucosal smears of female municipal sweepers with betel quid chewing practice (Journal of Pathology of Nepal, 2021)
Background: Oral cancer is common worldwide. Study of micronuclei in exfoliated buccal mucosal cells holds great scope in bio monitoring their carcinogenic potential. Betel quid chewing is one of the most common factors contributing to oral cancers. Ours being a developing country, a study was undertaken among female municipal sweepers, majority of who are betel quid chewers, unaware of the harmful effects of the same. We attempted to cytologically access the presence and compare the proportion of micronuclei in the right, left buccal mucosa and hard palate of female municipal sweepers with and without betel quid chewing practice.Materials and Methods: This was a cross sectional study with purposive sampling. Buccal smears were analysed from 30 betel quid chewers & non chewer females for micronuclei. Mean and standard deviationwere calculated. Independent T test was used for comparison between groups. P value less than 0.05 was considered statistically significant.Results: Frequency of micronuclei in betel quid chewers and non-chewers was 26.80+/-11.96 and 7.76+/-4.73. The frequency of total micronuclei per 250 cells in cases was 9.3+/-5.37 in right buccal mucosa, 9.43+/-5.66 in left buccal mucosa, 9.43+/- 5.66 in hard palate and 3.33+/- 2.88 in right buccal mucosa, 2.96+/-3.31 in left buccal mucosa, and 2.96+/-3.31 in hard palate in controls. Conclusions: The mean number of micronuclei in buccal mucosal cells of female municipal sweepers with betel quid chewing practice was significantly higher compared to controls reaffirming their carcinogenic potential and highlighting the need of early screening for oral cancer in susceptible groups.